Persepsi Pelaku UMKM di Desa Sumurmati Tentang Literasi Keuangan - Johan Oktavian; Raden Johnny Hadi Raharjo (Cv. Utility Project Solution, 2023)
Financial Literacy is one of the basic needs for everyone to be able to manage their finances properly and well. Not all people understand financial literacy. This is caused by several factors that become habits in society. The perception of the Sumurmati Village community about financial literacy still does not fully understand financial literacy. Communities prefer to own assets in the form of livestock or land rather than using financial products provided by financial institutions or others. This is influenced by various natural and human conditions that exist around the community. That way it will make a decision for every community to manage their finances and the risks that will be accepted by the residents of Sumurmati Village. There are also significant differences in managing finances in villages and cities. This is due to the understanding and perception of each individual regarding financial literacy. This study focuses on the perceptions of MSME actors in Sumurmati Village about how MSME actors manage their finances and what perceptions of financial literacy they understand.